Low cost-hydroponic fodder - Venkataramanan, R; Jemima, Rachel; Sundaram, S Meenakshi (Indian Farming, 2020)
Fodder availability throughout the year is essential to maintain any livestock enterprise. Landless farmers face acute shortage of fodder and intermittent periods of fodder shortage leads to long standing losses in production and reproduction. Hydroponics, the science of soilless agriculture caters to the needs of landless farmers to produce nutritious green fodder with less water and no land. This system is especially useful to small farmers with one or two milch animals. This paper aims at describing a low cost hydroponic system developed at UIIC, LFC, TANUVAS, Chennai to produce hydroponic green maize fodder.